Baltic - Black Sea Area as a Geopolitical Reality: Does It Exist? - Doroshko, Mykola; Tsyrfa, Iuliia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
As the social and political transformations observed in the modern world have recently made current the issue of formation of new geopolitical regions, the Baltic – Black Sea Area deserves particular attention because the geopolitical status of this junction territory still remains questionable. The geopolitical boundaries of the Baltic – Black Sea Area are constantly changing not only functionally, but also structurally, which is why it can be considered as a specific geopolitical formation located at the junction of the two geopolitical mega-regions of Western Europe and Northern Eurasia. This area is highly fragmented and still undergoing very painful political, cultural, and economic transformations. The power competition between Russia, NATO and the EU, as well as the region’s historical legacy have determined the path of its development. As a result, the Baltic – Black Sea Area does not have any system of political division or economic management, but close connections between the countries located there and many spheres of their common interest promote comprehensive cooperation and dialogue on a variety of issues. If their cooperation leads to multilateral relationships based on the principle of the sovereign equality of states which are trying to expand the scope of their collaboration and limit the scope of confrontation, they could organize a system of complementary elements which provide synergies and ensure the existence of the Baltic – Black Sea Area as a geopolitical reality.

Ponieważ przemiany społeczne i polityczne, jakie obserwujemy we współczesnym świecie, uaktualniły w ostatnim czasie kwestię powstawania nowych regionów geopolitycznych, obszar mórz Bałtyckiego i Czarnego zasługuje na szczególną uwagę, ponieważ status geopolityczny tego znajdującego się na rozdrożach obszaru jest wciąż dyskusyjny. Geopolityczne granice obszaru mórz Bałtyckiego i Czarnego nieustannie się zmieniają nie tylko funkcjonalnie, ale także strukturalnie: można więc uznać ten obszar za specyficzną formację geopolityczną, która znajduje się na styku dwóch geopolitycznych megaregionów – Europy Zachodniej i Północnej Eurazji. Obszar ten jest głęboko podzielony i nadal przechodzi bardzo bolesne przemiany polityczne, kulturowe i gospodarcze. Rywalizacja o władzę między Rosją, NATO i UE, a także dziedzictwo historyczne tego rejonu uwarunkowały ścieżkę jego rozwoju. W efekcie w obszarze mórz Bałtyckiego i Czarnego nie istnieje żaden system podziału politycznego czy zarządzania gospodarką, ale bliskie związki znajdujących się tam krajów i wiele obszarów wspólnych zainteresowań sprzyjają wszechstronnej współpracy i dialogowi w różnorakich kwestiach. Jeśli ich współpraca przybierze formę wielostronnych relacji opartych na zasadzie suwerennej równości państw, które starają się poszerzyć zakres współpracy i ograniczyć pole konfrontacji, państwa te będą w stanie stworzyć system komplementarnych elementów zapewniających efekt synergii, urzeczywistniając powstanie obszaru mórz Bałtyckiego i Czarnego stanowiących rzeczywisty byt geopolityczny.
Obszar Mórz Bałtyckiego i Czarnego jako fakt geopolityczny: czy on w ogóle istnieje?
Keywords: Baltic Sea; Black Sea; Baltic – Black Sea Area; geopolitical reality; multilateral cooperation; Morze Bałtyckie; Morze Czarne; obszar mórz Bałtyckiego i Czarnego; rzeczywistość geopolityczna; współpraca wielostronna